Perancangan dan Modelling Karakter Maskot STMIK Bumigora Mataram - R. Fanny Printi Ardi; Rr. Fentya Aristalia Hartini (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2019)
STMIK Bumigora Mataram is one of the universities in NTB, which is capable of competing with other universities. In addition, in the future, STMIK Bumigora Mataram will become an international college that can reduce scientific disparity and resources. STMIK Bumigora Mataram is one of the most popular universities in Indonesia especially in the NTB region. Every year STMIK Bumigora Mataram actively promotes related to new student registration. The promotional media used at that time by STMIK Bumigora Mataram in the past 2 years in the form of brochures, advertisements, calendars, posters, websites and promotions go to scholl, then every campus needs to have a different promotional tool than before so that in the future STMIK bumigora mataram needs a promotional media in the form of mascots by reflecting on a particular company or institution that can make it a symbol that is easily remembered by the community. STMIK Bumigora Mataram is the only university that will have a mascot in the NTB region. This mascot character is in the form of 3D animation object, as a representative character representing STMIK Bumigora Mataram which is easier to recognize, for this reason it is necessary to create a mascot character as a promotional tool for STMIK Bumigora Mataram which can be a promotional activity. The design of this mascot character uses the Vilamil-Molina method, a multimedia development method that starts from the concept stage, planning, usage development until the trial stage in building application software using blender software and by utilizing Photoshop software that is used to create textures, then produce a video